A Review on Synthesis of Nanocomposite Material - K Ghosh, Manoj; Bano, Sarvaree (International Journal of Psychosocial Rehabilitation, 2021)
This paper mainly focusing on the synthesis of poly-matirx metal oxide prepared bySol-gel method,Co-precipitation method and Hydrothermal method. This review is designed to research characterization,synthesis and applications of polymatrix nanocomposite material. Metal oxide nanocomposites have the materials with the range of applications in the industrial sector. For the formation of complex matrix co-precipitation is the simplest method. Characterization of this materials are with the help of XRD, atomic force microscopyand TGA method. Which explain the particle size , thermal stability and morphology etc.